Gugatan Ganti Kerugian dalam Kasus Pencemaran Nama Baik menurut Kitab Undang-Undang Hukum Perdata - I Made Heriyana; Anak Agung Sagung Dewi; Ni Made Puspasutari Ujianti (Warmadewa Press, 2020)
Legal protection against defamation victims in the national legal system has not obtained adequate protection. Whereas in the concept of legal state as a form of protection against victims of crime must obtain a large portion as a state of protection against the community. Based on the background of the problem described above. It can be formulated with the following problems 1) How is the indemnity claim made by criminal defamation? 2) How is the process of indemnity against defamation victims? Referring to the formulation of the problem then the type of research used in the writing is normative research. Methods used in the processing of legal materials namely the method of analysis of analytical decsriptive data. The reimbursement of damages incurred upon the name of the defamation is set out in the Civil Code of article 1372-1380 as a form of unlawful deed as stipulated in article 1365 of the Civil Code. There is a date of tax assessment to file a lawsuit for an insult i.e. a lawsuit must be filed within one year from the day of the deed and the perpetration of the act/insult by the plaintiff. Damages are intended to restore the condition of the victim so that it is in or back to such circumstances if there is no insult in other words intended to replace the lost or reduced victim of insult.